Supply chain practices on FMCG products of New Zealand Dairy Products Bangladesh Ltd. - Chowdhury, Md. Tarik (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.